Production of Borreliacidal Antibody to Outer Surface Protein A In Vitro and Modulation by Interleukin-4 - Munson, Erik L. (American Society for Microbiology, 2000)
Borreliacidal antibody production is one of several parameters for establishing the effectiveness of Borrelia burgdorferi vaccines. The production of borreliacidal antibody was studied in vitro by culturing immune lymph node cells with macrophages and B. burgdorferi. We showed that borreliacidal antibody, directed primarily against outer surface protein A (OspA), was readily produced by lymph node cells obtained from C3H/HeJ mice vaccinated with formalin-inactivated B. burgdorferi in aluminum hydroxide, but not recombinant OspA. Anti-OspA borreliacidal antibody was detected in supernatants of cultures of lymph node cells obtained on day 7 after vaccination, peaked on day 17, and rapidly declined. The borreliacidal activity was attributable to immunoglobulin G1 (IgG1), IgG2a, and IgG2b antibodies. When lymph node cells were treated with interleukin-4 (IL-4), production of borreliacidal antibody was inhibited but was unaffected by treatment with anti-IL-4 antibodies. These results suggest that other cytokines, but not IL-4, are mainly responsible for production of the secondary borreliacidal antibody response.